2020
DOI: 10.15253/2175-6783.20202144043
|View full text |Cite
|
Sign up to set email alerts
|

Measures used in intensive care units to prevent infection: an integrative review

Abstract: Objective: to verify measures used in intensive care units to prevent infection related to health care. Methods: integrative review based on the data sources LILACS, SCOPUS, PubMed Central, Science Direct, Web of Science and CINAHL, whose descriptors used were: Infection Control and Intensive Care Units. Sample consisting of 146 studies. Results: thematic categories related to the relevant infection prevention measures were listed, developed in Intensive Care Units: bloodstream infection prevention measures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…No tocante ao ano de publicação dos estudos identificados na scoping review, observou-se que a maioria dos artigos foram publicados nos últimos cinco anos, com níveis de evidência com grau forte de recomendação, de forma a representar uma discussão recente e apropriada da temática. Esse resultado pode estar relacionado com o maior interesse nos estudos relacionados à saúde ocular, com ênfase no olho seco/ressecamento ocular nos últimos anos, um cuidado por vezes negligenciado, principalmente em locais de cuidados críticos, como a UTI (1,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…No tocante ao ano de publicação dos estudos identificados na scoping review, observou-se que a maioria dos artigos foram publicados nos últimos cinco anos, com níveis de evidência com grau forte de recomendação, de forma a representar uma discussão recente e apropriada da temática. Esse resultado pode estar relacionado com o maior interesse nos estudos relacionados à saúde ocular, com ênfase no olho seco/ressecamento ocular nos últimos anos, um cuidado por vezes negligenciado, principalmente em locais de cuidados críticos, como a UTI (1,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Discussionunclassified
“…Para a determinação dos atributos críticos e identificação dos antecedentes e consequentes do conceito, foi realizada uma scoping review segundo as recomendações do JBI de 2020 (14) , utilizando os critérios estabelecidos no checklist Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) (15) . O estudo em questão foi registrado na plataforma de estudos Open Science Framework, sendo gerado um identificador sequencial correspondente de Uniform Resource Locator (osf.io/qtv79) (16) .…”
Section: Desenho De Estudounclassified
“…Regarding the year of publication of the studies identified in the scoping review, it was observed that most articles were published in the last five years, with levels of evidence with a strong degree of recommendation, in order to represent a recent and appropriate discussion of the subject. This result may be related to the greater interest in studies related to ocular health, with emphasis on dry eye/ ocular dryness in recent years, a care that is sometimes neglected, especially in critical care settings, such as the ICU (1,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) . Two attributes were identified to conceptually define the diagnosis Ocular dryness, such as tear film deficiency and ocular signs and/or symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the critical attributes and identify the antecedents and consequences of the concept, a scoping review was carried out according to the JBI 2020 recommendations (14) and using the criteria established in Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) (15) . The study in question was registered on the Open Science Framework study platform and a corresponding Uniform Resource Locator sequential identifier (osf.io/qtv79) was generated (16) .…”
Section: Methodsmentioning
confidence: 99%